IMPLEMENTATION OF REGIONAL REGULATION NUMBER 7 OF 2016 ON ENVIRONMENTAL CLEANLINESS AND BEAUTIFICATION IN AMUNTAI SELATAN DISTRICT, HULU SUNGAI UTARA REGENCY (Case Study on Special Waste in Environmental Cleanliness) - Rina Safitri; Agus Surya Dharma; Yusran Fahmi (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The implementation of Hulu Sungai Utara Regional Regulation No. 7 of 2016 in South Amuntai has not been optimal, marked by pollution due to the disposal and burning of wood waste from the furniture industry. This problem is triggered by low awareness among craftsmen and minimal socialization of the regulations. This study aims to analyze the implementation of the regulation and the factors that influence it in order to realize clean environmental governance. The results show that the implementation of Hulu Sungai Utara Regency Regional Regulation No. 7 of 2016 concerning the Implementation of Cleanliness and Environmental Beauty in South Amuntai District, particularly in waste management specifically for wooden furniture businesses, has generally been running quite well, but not optimally. First, in terms of the desired policy aspect, the clarity of the objectives and implementation rules for special waste management have not been fully understood by business actors, although the policy is considered quite appropriate to local conditions. Second, among the target group, the level of understanding, participation, and compliance of furniture business actors in managing wood sawdust and wood chip waste is still relatively low. Third, from the implementing organization's perspective, limited human resource quality, coordination, and facilities and infrastructure are the main obstacles to policy implementation. Fourth, environmental factors indicate community support for the furniture business as a livelihood, but a culture and habit of waste management that does not comply with regulations still persists. Supporting factors for policy implementation include clarity of objectives, local suitability, and awareness among some business actors, while inhibiting factors include low compliance, limited resources, facilities, and an unorganized waste management culture. It is recommended that the government improve outreach, supervision, and sanitation facilities, as well as improve compliance of business actors and the community in managing furniture waste in accordance with regional regulations in a sustainable manner.